From Money Growth to Consumer Spending: Forecasting with Divisia Monetary Aggregates - Zhengyang Chen (ZBW - Leibniz Information Centre for Economics, 2025)
This paper examines how money growth affects personal consumption using Divisia monetary aggregates. Using monthly U.S. data from 2000 to 2023, we find that changes in Divisia M4 significantly predict personal consumption expenditure, with a lag of three months. A 1% increase in Divisia M4 is associated with a 0.3% increase in consumption, controlling for macroeconomic factors. Through five-fold cross-validation, we demonstrate that Divisia-based forecasting models reduce prediction errors by 20% compared to models using the federal funds rate. Our findings suggest that broader monetary aggregates contain important predictive information for consumption dynamics, particularly when interest rates are low.
Keywords: E3; E; 330; Divisia money; Consumption; Forecasting